Relevance of Digital Transformation in the Libyan Health System: Implementation of an Electronic Health Record System (EHRS) - Aisha Saed Alatrash (African Journal of Advanced Pure and Applied Sciences, 2024)
One of the important reasons leading to the low quality of health services in some developing countries such as Libya is the challenges doctors face while diagnosing and treating patients. These challenges include collecting patients’ backgrounds as well as the difficulty of cooperating between hospitals and clinics, whether governmental or private. As a result, this study aims to identify the importance of digital transformation in the health sector and propose implementing an electronic health record (EHR) system to raise the quality of health services. Digital transformation provides a new way to deliver high-quality services, improve processes, and meet customers’ needs effectively, easily, effortlessly, and in less time. EHR system will centralize patients’ information in one database that any authorized doctor can access from any hospital, clinic, or medical centers. Therefore, doctors can know their patients' medical history, including disease, allergies, surgeries, immunizations, and comorbidities, as well as, medications being taken. In addition, information on some diseases can be shared along with patients’ experiences and treatment histories to provide as much information as possible to help treat difficult cases.